Body-worn cameras for police accountability: Opportunities and risks. Issue 6 (December 2015) - Coudert, Fanny; Butin, Denis; Le Métayer, Daniel
Abstract: The use of body-worn cameras by police forces around the world is spreading quickly. The resulting mobile and ubiquitous surveillance is often marketed as an instrument for accountability and an effective way of reducing violence, discrimination or corruption. It also involves remarkable potential for intrusion into the privacy of both individuals and police agents. We analyse the deployment of police body-worn cameras in five countries, investigate their suitability as an accountability tool given the associated privacy threats, and discuss the societal impact of their deployment as well as the risk of function creep.